Shen Gua's empiricism - Zuo, Ya 1982- (Harvard-Yenching Institute monograph series, 2018)
"Describes the life of Shen Gua, a distinguished renaissance man in China whose writing included remarkable "scientific" discoveries. Reveals the connection between Shen's life as an active statesman and his empirical inquiries, and provides insights into the dynamics between science and politics in the age of Neo-Confucianism"--Provided by publisher.